2013
DOI: 10.1098/rsif.2012.0913
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of plant fruit hooks

Abstract: Hook-like surface structures, observed in some plant species, play an important role in the process of plant growth and seed dispersal. In this study, we developed an elastic model and further used it to investigate the mechanical behaviour of fruit hooks in four plant species, previously measured in an experimental study. Based on Euler -Bernoulli beam theory, the forcedisplacement relationship is derived, and its Young's modulus is obtained. The result agrees well with the experimental data. The model aids i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Tansley insight New Phytologist that increase friction with the soil (Grohmann et al, 2019), potentially allowing them to remain within the soil in a particular location. Indeed, a common alternative to wind dispersal is to stick to animal coats or soil particles via hooks (Gorb & Gorb, 2002;Chen et al, 2013;Horbens et al, 2015) or glue (Western, 2012;Kreitschitz et al, 2015;Lenser et al, 2016;Arshad et al, 2019). In Martyniaceae fruit, a curved structure with transverse fibres allows bending behaviour while hooking, and longitudinally arranged sclerenchyma appear to enhance tensile strength (Horbens et al, 2015).…”
Section: Reviewmentioning
confidence: 99%
“…Tansley insight New Phytologist that increase friction with the soil (Grohmann et al, 2019), potentially allowing them to remain within the soil in a particular location. Indeed, a common alternative to wind dispersal is to stick to animal coats or soil particles via hooks (Gorb & Gorb, 2002;Chen et al, 2013;Horbens et al, 2015) or glue (Western, 2012;Kreitschitz et al, 2015;Lenser et al, 2016;Arshad et al, 2019). In Martyniaceae fruit, a curved structure with transverse fibres allows bending behaviour while hooking, and longitudinally arranged sclerenchyma appear to enhance tensile strength (Horbens et al, 2015).…”
Section: Reviewmentioning
confidence: 99%
“…It showed that the delamination strength (at rupture) of the interlocking barbules was dependent on the interaction between the bow-and hook-barbules, and the hooklets on the hook-barbules play an important role. In respect of hooklet mechanics, researchers have reported mechanical behaviors of single hooklets [7,8], however, they are plants fruits for dispersing their seeds. Here, instead of studying the developmental morphology of feathers, we aimed at understanding the robustness of interlocking hook-and bow-barbule arrays in bird feathers, using a hierarchical analytical model (hook-and bowbarbules connected by microhook arrays).…”
Section: Introductionmentioning
confidence: 99%
“…The deformations of the barbs and barbules were studied, and then coupled to develop a theoretical framework to predict critical delamination forces between the barbules. It is worth mentioning that the model does not include the exact hooklet geometry, and only considers the equivalent friction effect produced by the hooklets between the barbules as reasonably suggested by [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2a [21] can be mimicked for conceptual design of stiffness controllable thin layers based on electro-active Velcros mechanisms. Biological fastening mechanisms can be categorized into several groups according to their morphology, such as (1) hooks, (2) lock or snap, (3) clamp, (4) spacer or expansion anchor, (5) suction, and (6) dry adhesion [5].…”
Section: Bio-inspired Design and Fabricationmentioning
confidence: 99%